Experimental study on the degradation mechanism of LaCoO3-based symmetric supercapacitors. Issue 41 (20th July 2021) - Chen, Xu; Su, Qiwei; Yu, Jipan; Wei, Mingrui; Guo, Guanlun; Wang, Yun
Abstract : Cycling tests for LaCoO3 -based symmetric supercapacitors were carried out. The change in the valence state of Co in the electrode surface active material, LaCoO3, before and after the cycling test was investigated by X-ray photoelectron spectroscopy. Abstract : In this paper, LaCoO3 powders were prepared by the urea combustion method and used as electrode materials for supercapacitors. The effect of the potential window and the current density on the performance degradation of LaCoO3 electrodes during the cycling test was analyzed. The degradation mechanism of LaCoO3 -based symmetric supercapacitors was discussed. The results of the cycling test show that: with the increase in potential window and current density, the performance degradation in the cycling test becomes more intense. The results of cyclic voltammetry tests, galvanostatic charge–discharge tests, X-ray photoelectron spectroscopy tests and KOH electrolyte concentration measurements before and after the cycling test show that the degradation of the supercapacitors is mainly caused by the occurrence and accumulation of irreversible redox reactions during the charge and discharge process, which reduces the ratio of Co 2+ /Co 3+ and the number of oxygen vacancies.